Thin-film solar cell packaged by ultra-thin glass and preparation method of thin-film solar cell
Through the ultra-thin glass packaging structure, combined with the inorganic material passivation layer and the organic material buffer layer, the stability and flexibility problems of thin-film solar cells are solved, and efficient water-oxygen barrier and photoelectric conversion efficiency are achieved, which is suitable for flexible electronic products.
Patent Information
- Application Number
- CN202411276939.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
Thin-film solar cells are insufficient instability, especially due to water absorption, thermal decomposition, metal ion migration and external factors, it is difficult to effectively encapsulate and protect in flexible electronic products.
Adopt ultra-thin glass packaging structure, including the bottom and top ultra-thin glass, inorganic material passivation layer, organic material buffer layer and packaging adhesive layer, and a dense inorganic packaging layer is formed through laser low-temperature sintering technology to improve water and oxygen barrier properties and Flexible.
It realizes high stability, flexibility and lightweight of thin-film solar cells, significantly improves their water-oxygen resistance and photoelectric conversion efficiency, extends their service life, and is suitable for bending and folding applications.
Smart Images

Figure CN119136577A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photovoltaic technology, and in particular relates to a solar cell and a preparation method thereof. Background Art
[0002] With the rapid development of science and technology, various new consumer electronic products have emerged, such as wearable devices, flexible electronics, plastic electronics, and organic electronics. These products have been widely welcomed and applied because of their lightness, flexibility, and high efficiency. However, the popularity of these new electronic products has also brought new challenges, especially in terms of energy supply. In order to meet the demand of equipment for lighter, more flexible, and more efficient energy supply devices, the application of thin-film solar cells in these fields has also emerged, and its unique characteristics perfectly meet this market demand. Thin-film solar cells are solar cells manufactured using thin-film technology, and their thickness is usually only a few microns to tens of microns, which is much thinner than traditional silicon solar cells. This type of battery is not only light in weight, but also has good flexibility and can be bent and folded, making it very suitable for use in wearable devices and flexible electronic products.
[0003] The main types of thin-film solar cells include perovskite solar cells (PSC), organic solar cells (OPV) and cadmium telluride solar cells. Among these types, PSC and OPV are superior to traditional crystalline silicon cells in thickness and cost, but the main challenge they face is insufficient stability. The instability of thin-film solar cells is mainly caused by several factors: strong water absorption, easy thermal decomposition, easy migration of metal ions, and external factors (ultraviolet decomposition and yellowing caused by light). Therefore, thin-film solar cells also have higher requirements for product packaging. In the application field of thin-film solar cells, organic packaging materials such as ethylene-vinyl acetate copolymer (EVA) or polyolefin elastomer (POE) are mainly used to achieve packaging protection. Due to the water and oxygen permeability of organic materials (10 -3 g / m 2 .day) is significantly higher than inorganic glass materials (10 -5 g / m 2 .day), therefore, inorganic glass has a better performance in encapsulating and protecting thin-film solar cells. However, it is difficult to prepare flexible solar cells with good flexibility using inorganic glass encapsulation, and the water and oxygen permeability of the encapsulation side is still difficult to ensure, which will affect the stability of the solar cell. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a thin-film solar cell encapsulated by ultra-thin glass with good stability, good flexibility and light weight and a preparation method thereof.
[0005] In order to solve the above technical problems, the technical solution proposed by the present invention is:
[0006] A thin-film solar cell encapsulated by ultra-thin glass comprises a bottom layer of ultra-thin glass, a solar cell, an inorganic material passivation layer, an organic material buffer layer, an encapsulation adhesive layer and a top layer of ultra-thin glass, wherein the solar cell is arranged on the bottom layer of ultra-thin glass, the inorganic material passivation layer cover is arranged on the solar cell, the organic material buffer layer cover is arranged on the inorganic material passivation layer, the top layer of ultra-thin glass is arranged on the organic material buffer layer, and the encapsulation adhesive layer is arranged on the periphery of the organic material buffer layer and is located between the bottom layer of ultra-thin glass and the top layer of ultra-thin glass.
[0007] In the above-mentioned thin film solar cell sheet, preferably, the total thickness is less than 500.0 μm, and the bending radius is less than 50.0 cm. The above-mentioned structure adopted by the present invention allows the total thickness to be less than 500.0 μm, and the bending radius to be less than 50.0 cm, and has the advantages of ultra-thinness, lightness, and good flexibility.
[0008] In the above-mentioned thin-film solar cell, preferably, the bottom layer ultra-thin glass and the top layer ultra-thin glass are one of soda-lime glass, high aluminum glass or low-alkali glass, with a thickness of 10.0-150.0 μm, a visible light band transmittance greater than 88.0%, a bending radius of no more than 10.0 cm, and a haze of no more than 0.5. Due to the influence of the size effect, when the thickness of the inorganic glass material is reduced to a certain extent (less than 150.0 μm), it will show better bending flexibility, providing an ideal flexible substrate for thin-film solar cells. Compared with traditional materials such as boric acid glass, this specific type of inorganic glass material has higher water and oxygen barrier properties, which means that it can more effectively block the penetration of moisture and oxygen. In addition, this material also has a smaller bending radius, which makes it perform well in application scenarios that require bending or folding. More importantly, this type of inorganic glass material also has the characteristics of high light transmittance and low haze, which makes it have an advantage in improving photoelectric conversion efficiency. High transmittance ensures that more light can penetrate the material, thereby improving the light absorption capacity of solar cells, while low haze means that the surface of the material is more transparent, reducing the scattering of light inside the material, further optimizing the photoelectric conversion efficiency.
[0009] In the above-mentioned thin-film solar cell, preferably, the solar cell is prepared in situ on the bottom layer of ultra-thin glass, and the solar cell includes a transparent conductive layer, a hole transport layer, a light absorption layer, an electron transport layer and a top electrode from bottom to top.
[0010] In the above-mentioned thin-film solar cell, preferably, the transparent conductive layer comprises any one of ITO, FTO or AZO, and has a thickness of 30.0-50.0 nm; the hole transport layer comprises spiro-OMeTAD, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] or NiO X Any one of, with a thickness of 20.0-100.0nm; the light absorption layer includes any one of organic-inorganic hybrid perovskite materials or organic semiconductor materials, with a thickness of 100.0-700.0nm; the electron transport layer includes any one of tin oxide, titanium oxide or zinc oxide, with a thickness of 20.0-100.0nm; the metal electrode includes any one of Au or Ag, with a thickness of 3.0-10.0μm. By precisely controlling the thickness between each layer, the flexibility of each layer can be effectively achieved, and the ultra-thinness and overall flexibility of the overall structure are further promoted. Based on long-term experimental studies, it is found that the combination of the above thicknesses can achieve a better balance between bending flexibility and solar cell photoelectric conversion efficiency.
[0011] In the above-mentioned thin film solar cell sheet, preferably, the inorganic material passivation layer is any one of a MgF2 layer, a Si3N4 layer, a SiO2 layer, a TiO2 layer and an Al2O3 layer prepared by atomic layer deposition, magnetron sputtering or thermal evaporation, with a thickness of 10.0-100.0 nm. By adopting the above-mentioned thin film deposition technology, a dense inorganic coating with molecular arrangement can be prepared. This coating plays an important role in two main aspects. First, it can effectively block the diffusion of water molecules and oxygen, thereby reducing the erosion of these harmful substances on the internal structure of the solar cell. Secondly, this dense inorganic coating can effectively isolate the diffusion between the organic buffer layer and the metal electrode and the electron transport layer material in the solar cell, preventing the two organic materials from having unnecessary chemical reactions or mutual erosion. The coating can maintain the independence and integrity of each functional layer, and can also improve the structural stability and service life of the entire solar cell device. In addition, the inorganic material passivation layer is a brittle material, and the size effect of the material can also maintain good bending flexibility at low thickness.
[0012] In the above-mentioned thin-film solar cell, preferably, the material of the organic material buffer layer includes any one of ethylene-vinyl acetate copolymer, polyolefin elasticity or OCA optical glue, with a thickness of 20.0-100.0 μm. The thin-film solar cell using ultra-thin glass as the packaging material has good bending performance. However, when the cell is bent, stress concentration points will inevitably be generated in certain areas. These stress concentration points will cause minor damage between the inorganic glass layers, which will lead to failure and performance degradation of the solar cell. Filling the gap between the double-layer ultra-thin glass with organic materials can effectively disperse stress, reduce the formation of stress concentration points, and absorb and alleviate the minor deformation generated during the bending process to a certain extent, thereby protecting the cell from damage; in addition, selecting packaging materials with water vapor barrier properties, such as POE, EVA and OCA, can also enhance the packaging protection effect of the solar cell. In order to better play the above role, the organic material buffer layer of the present invention needs to be arranged between the double-layer ultra-thin glass and have a large area of contact with the double-layer ultra-thin glass.
[0013] In the above-mentioned thin-film solar cell, preferably, the encapsulation adhesive layer is prepared by laser low-temperature sintering of inorganic adhesive (such as nickel-based, cobalt-based, iron-based alloy) or UV curing organic adhesive (such as phenyl silicone resin, epoxy acrylic resin), wherein the laser wavelength is 800.0-1600.00nm. More preferably, the encapsulation adhesive layer is prepared by laser low-temperature sintering of inorganic adhesive. The core principle of laser low-temperature sintering technology is to utilize the absorption characteristics of inorganic materials to lasers of specific wavelengths. When these inorganic materials are exposed to a laser beam, they absorb the light energy of the corresponding wavelength and convert it into heat energy, thereby achieving the sintering effect. This conversion process causes the inorganic material to melt, that is, the material changes from a solid state to a liquid state. Subsequently, through the cooling and solidification process, the molten inorganic material solidifies again to form a dense structure. In this process, the inorganic material is sandwiched between two layers of ultra-thin glass. The advantage of this structure is that a very dense and uniform inorganic encapsulation layer can be formed between ultra-thin glass through laser low-temperature sintering technology. This encapsulation layer has excellent water and oxygen barrier properties, which can effectively prevent the penetration of moisture and oxygen, thereby protecting internal sensitive components or materials from the influence of the external environment.
[0014] As a general technical concept, the present invention also provides a method for preparing the above-mentioned ultra-thin glass encapsulated thin-film solar cell, comprising the following steps:
[0015] S1. Clean the bottom ultra-thin glass;
[0016] S2, preparing solar cells on the bottom ultra-thin glass;
[0017] S3, preparing an inorganic material passivation layer on the surface of the solar cell;
[0018] S4, covering the surface of the inorganic material passivation layer with an organic material buffer layer;
[0019] S5. Print a packaging adhesive in the shape of a circular frame on the top layer of ultra-thin glass, attach it to the bottom layer of ultra-thin glass, and use laser low-temperature sintering of inorganic adhesive or UV curing of organic adhesive to form a packaging adhesive layer to obtain a thin-film solar cell.
[0020] In the above preparation method, preferably, in step S5, when using laser low-temperature sintering of the inorganic binder, the distance between the inorganic binder layer and the solar cell is not less than 2.0 mm. During the laser low-temperature sintering of the inorganic binder, the local temperature will exceed 400°C. By controlling the distance from the solar cell, the negative impact of the sintering high temperature on its layers can be avoided.
[0021] Aiming at the application market of thin-film solar cells encapsulated by ultra-thin glass, the present invention proposes a structure with ultra-thin glass as the core to achieve reliability and flexibility of solar cell encapsulation, which is particularly based on the following ideas and research:
[0022] First, traditional flexible solar cells or modules usually use polyethylene terephthalate plastics (PET), polyethylene naphthalate (PEN) or polyimide (PI) as substrate materials. After the thin-film solar cells are manufactured, these modules use high-performance ethylene-vinyl acetate copolymer (EVA) or polyolefin elastomer (POE) as the upper encapsulation material to protect the solar cells. However, this practice often ignores the water and oxygen barrier of the lower substrate, which may lead to the failure of the solar cell. Compared with inorganic materials, all organic material substrates have a common fatal weakness: insufficient stability. Under heat and light conditions, the composition and film morphology of the material are prone to change, and are susceptible to aging due to moisture and gas. The present invention proposes an innovative method, that is, inorganic glass materials with excellent water and oxygen resistance are used in both the upper and lower layers of the solar cell, thereby significantly improving the long-term reliability of thin-film solar cells.
[0023] Second, as a flexible substrate for solar cells, it must have excellent optical properties and remain dimensional stable after undergoing various chemical environments and temperature changes in the preparation process, which poses a major challenge to organic flexible materials. Although under the same thickness or flexibility conditions, organic flexible substrates stand out for their better flexibility, lighter weight and stronger impact resistance, they also face some problems: first, the surface roughness is high (taking PET substrate as an example, about 150nm), and the surface protrusions will interfere with the upper transparent conductive layer, hole transport layer, light absorption layer, electron transport layer and top electrode and other multi-layer thin film structures, thereby causing local short circuits or defects in thin-film solar cells; second, the substrate is prone to deformation during subsequent processing, whether it is elastic deformation at high temperature or wrinkle deformation at low temperature, which will reduce the yield of the final product; finally, low water and oxygen barrier rate is the key to the high reliability of thin-film solar cells. Once water vapor penetrates, the photoelectric properties of the device will rapidly degrade. When having considerable flexibility, quality and impact resistance, the above-mentioned deficiencies can be perfectly replaced by the ultra-thin flexible glass used in the present invention.
[0024] Third, the thin-film solar cells encapsulated in double-layer ultra-thin glass can be protected from both the top and bottom. However, water and oxygen may still penetrate through the edges. The encapsulation adhesive layer, organic material buffer layer and inorganic material passivation layer proposed in the present invention all have additional encapsulation protection functions, and the layers work together to improve the stability and flexibility of the encapsulation structure. First, the encapsulation adhesive layer is formed by laser low-temperature sintering of the inorganic adhesive, and the inorganic encapsulation layer also exhibits a low water and oxygen permeability. Secondly, the organic material buffer layer adopts high-performance organic materials, which not only blocks water and oxygen, but also releases the local stress of the rigid glass during flexible bending, thereby realizing a thin and rollable structure. Finally, the inorganic material passivation layer adopts a deposited dense inorganic coating, which not only blocks water vapor, but also prevents the organic matter in the buffer layer from migrating and reacting with the organic matter in the thin-film solar cell, thereby ensuring the stability of the thin-film solar cell.
[0025] The ultra-thin glass-encapsulated thin-film solar cell and its preparation method of the present invention are intended to provide an ultra-thin and flexible high-efficiency thin-film solar cell technology for the emerging consumer electronics market. By utilizing the water and oxygen barrier properties of inorganic glass and multiple water and oxygen barrier structures, the layers work together to solve the stability problem of thin-film solar cells, thereby enhancing their reliability; at the same time, by making the glass ultra-thin, the size effect of the material is fully utilized, and the thickness of each layer is precisely controlled and adjusted to achieve the best state of flexibility, thereby achieving the flexibility and lightness of thin-film solar cells, providing a feasible solution for the market.
[0026] Compared with the prior art, the advantages of the present invention are:
[0027] 1. The thin-film solar cell encapsulated by ultra-thin glass of the present invention uses ultra-thin glass as the encapsulation material, which has significantly improved the water and oxygen resistance compared to the traditional all-organic encapsulation structure. By adopting the encapsulation strategy of the upper and lower layers of inorganic glass substrates, all-round protection of solar cells is achieved. This encapsulation method is more advanced than the existing encapsulation technology. The existing technology usually only uses high-performance encapsulation materials such as POE (polyolefin elastomer), EVA (ethylene-vinyl acetate copolymer) and OCA (optically transparent adhesive) on the upper substrate, while the lower substrate uses PET (polyethylene terephthalate), PEN (polyethylene naphthalate) or PI (polyimide). In contrast, the double-layer ultra-thin glass encapsulation strategy of the present invention can further improve the encapsulation protection effect of solar cells, thereby ensuring the long-term reliability and stability of the device.
[0028] 2. The thin-film solar cell encapsulated by the ultra-thin glass of the present invention has excellent flexibility and realizes the bending performance of the overall structure. The present invention makes full use of the size effect of the material and has a certain degree of flexibility. At the same time, in order to improve the bending performance, the present invention provides an organic material buffer layer in the middle of the double-layer ultra-thin glass, which can release stress during the bending process and act as a buffer layer. It can effectively absorb and disperse stress, thereby avoiding breakage and damage that may be caused by rigid contact, and further improving the flexibility of the structure.
[0029] 3. The thin-film solar cell encapsulated by ultra-thin glass of the present invention has comprehensively improved the encapsulation effect of the overall device through multiple structural designs. Specifically, the use of inorganic glass materials as the upper and lower substrates, the use of encapsulation adhesive layer technology to achieve edge sealing, the introduction of high-performance organic material buffer layers, and the design of a molecular-level dense inorganic material passivation layer are all to effectively block the damage of water and oxygen to thin-film solar cells, ensure that solar cells can maintain excellent performance under various environmental conditions, and extend their service life.
[0030] In general, the thin-film solar cell encapsulated by the ultra-thin glass of the present invention enables the solar cell to have the remarkable characteristics of ultra-thin structure and flexibility, and improves the long-term stability and reliability of the thin-film solar cell, which is of great significance for the practical application of thin-film solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 It is a schematic diagram of the structure of a thin-film solar cell encapsulated by ultra-thin glass of the present invention.
[0033] Figure 2 This is an appearance diagram of a thin-film solar cell in Example 1 of the present invention.
[0034] Figure 3 This is a SEM image of the light absorbing layer in Example 1 of the present invention.
[0035] Figure 4 This is a SEM image of the cross section of the light absorbing layer in Example 1 of the present invention.
[0036] Figure 5 Schematic diagram of the change of the photoelectric efficiency of the thin-film solar cell with the number of bending times in Example 1 of the present invention.
[0037] Legend
[0038] 1. Bottom layer of ultra-thin glass; 21. Transparent conductive layer; 22. Hole transport layer; 23. Light absorption layer; 24. Electron transport layer; 25. Top electrode; 3. Inorganic material passivation layer; 4. Organic material buffer layer; 5. Encapsulation adhesive layer; 6. Top layer of ultra-thin glass. DETAILED DESCRIPTION
[0039] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0040] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0041] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0042] Embodiment 1:
[0043] like Figure 1As shown, the thin-film solar cell encapsulated by ultra-thin glass of the present embodiment comprises a bottom layer of ultra-thin glass 1, a solar cell, an inorganic material passivation layer 3, an organic material buffer layer 4, an encapsulation adhesive layer 5 and a top layer of ultra-thin glass 6. The solar cell is arranged on the bottom layer of ultra-thin glass 1, the inorganic material passivation layer 3 is covered on the solar cell, the organic material buffer layer 4 is covered on the inorganic material passivation layer 3, the top layer of ultra-thin glass 6 is arranged on the organic material buffer layer 4, and the encapsulation adhesive layer 5 is arranged on the periphery of the organic material buffer layer 4 and between the bottom layer of ultra-thin glass 1 and the top layer of ultra-thin glass 6. The solar cell is prepared in situ on the bottom layer of ultra-thin glass 1, and the solar cell comprises a transparent conductive layer 21, a hole transport layer 22, a light absorption layer 23, an electron transport layer 24 and a top electrode 25 from bottom to top. The appearance of the thin-film solar cell encapsulated by ultra-thin glass of the present embodiment is shown in FIG. Figure 2 shown.
[0044] The method for preparing the thin-film solar cell encapsulated by ultra-thin glass in this embodiment comprises the following steps:
[0045] In the first step, the soda-lime ultra-thin glass is cleaned and plasma treated to obtain a clean lower substrate, wherein the ultra-thin glass has a thickness of 150.0 μm, a transmittance in the visible light band of 88.2%, a bending radius of 10.0 cm, and a haze of 0.5.
[0046] In the second step, a layer of FTO is sputtered on the surface of the ultra-thin glass with a thickness of 50.0nm to obtain a transparent conductive layer; on the above transparent conductive layer, a spiro-OMeTAD coating is prepared by a slit coating process with a thickness of 100.0nm to obtain a hole transport layer; on the basis of the above hole transport layer, an organic-inorganic hybrid perovskite is prepared by a slit coating process as a light absorption layer with a thickness of 700.0nm; on the surface of the above light absorption layer, an electron transport layer is obtained by sputtering tin oxide with a thickness of 100.0nm; finally, a metal electrode with a thickness of 10.0μm is obtained by thermal evaporation of Au. Through the above process flow, an in-situ prepared thin-film solar cell can be obtained.
[0047] In the third step, Al2O3 is deposited by atomic layer deposition on the above-mentioned in-situ prepared thin-film solar cell to obtain a dense coating with a thickness of 50.0 nm as an inorganic material passivation layer.
[0048] In the fourth step, ethylene-vinyl acetate copolymer (EVA) is laminated on the inorganic material passivation layer, wherein the film thickness is 100.0 μm.
[0049] The fifth step is to clean the 100.0μm thick soda-lime ultra-thin glass to obtain a clean upper substrate, and screen print an inorganic binder circular frame on the surface of the upper substrate, wherein the designed circular frame is 2.0mm away from the edge of the thin-film solar cell. After the upper substrate is bonded, the inorganic binder area is sintered at low temperature using a laser, and the laser wavelength is 1100.00nm to obtain an ultra-thin glass encapsulated thin-film solar cell.
[0050] Figure 3 is a SEM image of the light absorbing layer in this embodiment, Figure 4 : is a SEM image of the cross section of the light absorbing layer in this embodiment, which can prove that its thickness meets the requirements of this embodiment.
[0051] The photoelectric conversion efficiency of the thin-film solar cell encapsulated in the ultra-thin glass was measured to be 20.9%. The total thickness of the structure was 361.0 μm, the bending radius was 50.0 cm, and after 10,000 bends, the photoelectric conversion efficiency dropped by less than 10.0%. The photoelectric efficiency changed with the number of bends as shown in the figure. Figure 5 At the same time, when the solar cell is placed in a high temperature (85°C) and high humidity (85%) environment, after 200 hours and 1000 hours, its photoelectric conversion efficiency is 20.7% and 19.8% respectively, and the maximum decay is 5.2%, which proves its excellent stability and good reliability.
[0052] Embodiment 2:
[0053] The structure of the thin-film solar cell encapsulated by ultra-thin glass in this embodiment is the same as that in the first embodiment.
[0054] The method for preparing the thin-film solar cell encapsulated by ultra-thin glass in this embodiment comprises the following steps:
[0055] In the first step, the high-aluminum glass ultra-thin glass is cleaned and plasma treated to obtain a clean lower substrate, wherein the ultra-thin glass has a thickness of 10.0 μm, a transmittance of 92.2% in the visible light band, a bending radius of 5.0 cm, and a haze of 0.4.
[0056] In the second step, a layer of ITO is sputtered on the surface of the ultra-thin glass with a thickness of 30.0nm to obtain a transparent conductive layer; on the transparent conductive layer, a poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] coating is prepared by a slit coating process with a thickness of 20.0nm to obtain a hole transport layer; on the basis of the hole transport layer, an organic semiconductor is prepared by a slit coating process as a light absorption layer with a thickness of 500.0nm; on the surface of the light absorption layer, titanium oxide is sputtered to obtain an electron transport layer with a thickness of 20.0nm; finally, a metal electrode with a thickness of 3.0μm is obtained by thermal evaporation of Au. Through the above process flow, an in-situ prepared thin-film solar cell can be obtained.
[0057] In the third step, Si3N4 is magnetron sputtered on the above-mentioned in-situ prepared thin-film solar cell to obtain a dense coating with a thickness of 100.0 nm as an inorganic material passivation layer.
[0058] In the fourth step, polyolefin elastomer (POE) is laminated on the inorganic material passivation layer, wherein the thickness of the adhesive film is 20.0 μm.
[0059] The fifth step is to clean the 150.0μm thick high aluminum ultra-thin glass to obtain a clean upper substrate, and screen print an inorganic binder circular frame on the surface of the upper substrate, wherein the designed circular frame is 4.0mm away from the edge of the thin-film solar cell. After the upper substrate is bonded, the inorganic binder area is sintered at low temperature using a laser, and the laser wavelength is 1600.00nm to obtain an ultra-thin glass encapsulated thin-film solar cell.
[0060] The total thickness of the thin-film solar cell encapsulated by the ultra-thin glass is about 184.0 μm, the photoelectric conversion efficiency is 21.4%, the bending radius is 40.0 cm, and after being bent 10,000 times, the photoelectric conversion efficiency decreases by less than 10.0%.
[0061] Embodiment 3:
[0062] The structure of the thin-film solar cell encapsulated by ultra-thin glass in this embodiment is the same as that in the first embodiment.
[0063] The method for preparing the thin-film solar cell encapsulated by ultra-thin glass in this embodiment comprises the following steps:
[0064] In the first step, the low-alkali ultra-thin glass is cleaned and plasma treated to obtain a clean lower substrate, wherein the ultra-thin glass has a thickness of 100.0 μm, a transmittance in the visible light band of 90.2%, a bending radius of 8.0 cm, and a haze of 0.4.
[0065] In the second step, a layer of AZO is sputtered on the surface of the ultra-thin glass with a thickness of 40.0nm to obtain a transparent conductive layer; on the transparent conductive layer, a NiO2 coating is prepared by a slit coating process with a thickness of 60.0nm to obtain a hole transport layer; on the basis of the hole transport layer, an organic-inorganic hybrid perovskite is prepared by a slit coating process as a light absorption layer with a thickness of 100.0nm; on the surface of the light absorption layer, an electron transport layer is obtained by sputtering zinc oxide with a thickness of 60.0nm; finally, a metal electrode with a thickness of 7.0μm is obtained by thermal evaporation of Ag. Through the above process flow, an in-situ prepared thin-film solar cell can be obtained.
[0066] The third step is to obtain a dense coating with a thickness of 10.0 nm by thermal evaporation of SiO2 on the above-mentioned in-situ prepared thin-film solar cell as an inorganic material passivation layer.
[0067] In the fourth step, OCA optical adhesive is bonded to the inorganic material passivation layer, wherein the adhesive film thickness is 20.0 μm.
[0068] The fifth step is to clean the 150.0μm thick low-alkali ultra-thin glass to obtain a clean upper substrate, and screen print a circular frame of organic adhesive on the surface of the upper substrate, wherein the distance between the circular frame and the edge of the thin-film solar cell is designed to be 2.5mm. After the upper substrate is bonded, the adhesive area is irradiated with a UV lamp with a laser wavelength of 800.0nm to obtain an ultra-thin glass encapsulated thin-film solar cell.
[0069] The total thickness of the thin-film solar cell encapsulated by the ultra-thin glass is about 278.0 μm, the photoelectric conversion efficiency is 20.4%, the bending radius is 45.0 cm, and after being bent 10,000 times, the photoelectric conversion efficiency drops by less than 10%.
[0070] Comparative Example 1:
[0071] The thin-film solar cell encapsulated by ultra-thin glass in this comparative example is different from that in Example 1 in that it does not have an organic material buffer layer.
[0072] Comparative Example 2:
[0073] The thin-film solar cell encapsulated by ultra-thin glass in this comparative example is different from that in Example 1 in that it does not have an inorganic material passivation layer.
[0074] Comparative Example 3:
[0075] The thin-film solar cell of this comparative example is different from that of Example 1 in that the upper and lower ultra-thin glass substrates both use 0.3 mm glass plates.
[0076] Comparative Example 4:
[0077] The thin-film solar cell encapsulated by ultra-thin glass in this comparative example is different from that in Example 1 in that it does not have an encapsulation adhesive layer.
[0078] Comparative Example 5:
[0079] The thin-film solar cell encapsulated by ultra-thin glass in this comparative example is different from that in Example 1 in that the thickness of the inorganic material passivation layer is 160 nm.
[0080] The thin-film solar cells in Examples 1-3 and Comparative Examples 1-5 were tested for photoelectric conversion efficiency, bending times, and lifespan under high temperature (85°C) and high humidity (85%). The results are shown in Table 1. A 500W xenon lamp was used to simulate sunlight with an intensity of 100mW / cm 2 , after processing based on the JV curve, the photoelectric conversion efficiency (PCE) parameters were calculated.
[0081] Table 1: Performance data of thin film solar cells in Examples 1-3 and Comparative Examples 1-5
[0082]
[0083] It can be seen from Example 1 and Comparative Example 1 that when there is no organic material buffer layer, the thin-film solar cell has insufficient flexibility, which causes breakage and failure during the bending process; it can be seen from Example 1 and Comparative Example 2 that diffusion occurs between the organic material buffer layer and the solar cell at high temperature, resulting in serious attenuation of the photoelectric conversion efficiency; it can be seen from Example 1 and Comparative Example 3 that the upper and lower substrates that are too thick have excellent stability, but are easily damaged by bending; it can be seen from Example 1 and Comparative Example 4 that the edgeless encapsulation adhesive layer and the slow diffusion of water and oxygen will also cause the solar cell to slowly fail and the performance to decay. It can be seen from Example 1 and Comparative Example 5 that when the inorganic material passivation layer is thicker, the photoelectric conversion efficiency and stability are still relatively excellent; however, when the ultra-thin substrate is not damaged, the bending test still causes the device to fail, which is caused by the inorganic material passivation layer being broken and damaged during bending.
Claims
1. A thin-film solar cell encapsulated by ultra-thin glass, characterized in that: It includes a bottom layer of ultra-thin glass, a solar cell, an inorganic material passivation layer, an organic material buffer layer, a packaging adhesive and a top layer of ultra-thin glass, wherein the solar cell is arranged on the bottom layer of ultra-thin glass, the inorganic material passivation layer cover is arranged on the solar cell, the organic material buffer layer cover is arranged on the inorganic material passivation layer, the top layer of ultra-thin glass is arranged on the organic material buffer layer, and the packaging adhesive layer is arranged on the periphery of the organic material buffer layer and is located between the bottom layer of ultra-thin glass and the top layer of ultra-thin glass.
2. The thin film solar cell according to claim 1, characterized in that: The total thickness is less than 500.0μm and the bending radius is less than 50.0cm.
3. The thin film solar cell according to claim 1, characterized in that: The bottom layer ultra-thin glass and the top layer ultra-thin glass are one of soda-lime glass, high aluminum glass or low alkali glass, with a thickness of 10.0-150.0 μm, a visible light band transmittance greater than 88.0%, a bending radius no greater than 10.0 cm, and a haze no greater than 0.
5.
4. The thin film solar cell according to claim 1, characterized in that: The solar cell is prepared in situ on the bottom layer of ultra-thin glass, and the solar cell comprises a transparent conductive layer, a hole transport layer, a light absorption layer, an electron transport layer and a top electrode from bottom to top.
5. The thin film solar cell according to claim 4, characterized in that: The transparent conductive layer includes any one of ITO, FTO or AZO, and has a thickness of 30.0-50.0 nm; the hole transport layer includes spiro-OMeTAD, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] or NiO X The light absorption layer comprises any one of an organic-inorganic hybrid perovskite material or an organic semiconductor material, and the thickness is 100.0-700.0nm; the electron transport layer comprises any one of tin oxide, titanium oxide or zinc oxide, and the thickness is 20.0-100.0nm; the metal electrode comprises any one of Au or Ag, and the thickness is 3.0-10.0μm.
6. The thin-film solar cell according to claim 1, characterized in that: The inorganic material passivation layer is any one of a MgF2 layer, a Si3N4 layer, a SiO2 layer, a TiO2 layer and an Al2O3 layer prepared by atomic layer deposition, magnetron sputtering or thermal evaporation, and has a thickness of 10.0-100.0 nm.
7. The thin-film solar cell according to claim 1, characterized in that: The material of the organic material buffer layer includes any one of ethylene-vinyl acetate copolymer, polyolefin elasticity or OCA optical adhesive, and the thickness is 20.0-100.0 μm.
8. The thin-film solar cell according to claim 1, characterized in that: The packaging adhesive layer is prepared by laser low-temperature sintering of an inorganic adhesive or UV curing of an organic adhesive, wherein the laser wavelength is 800.0-1600.00 nm.
9. A method for preparing a thin-film solar cell encapsulated by ultra-thin glass according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Clean the bottom ultra-thin glass; S2, preparing solar cells on the bottom ultra-thin glass; S3, preparing an inorganic material passivation layer on the surface of the solar cell; S4, covering the surface of the inorganic material passivation layer with an organic material buffer layer; S5. Print a packaging adhesive in the shape of a circular frame on the top layer of ultra-thin glass, attach it to the bottom layer of ultra-thin glass, and use laser low-temperature sintering of inorganic adhesive or UV curing of organic adhesive to form a packaging adhesive layer to obtain a thin-film solar cell.
10. The preparation method according to claim 9, characterized in that: In step S5, when the inorganic adhesive is sintered at low temperature by laser, the distance between the inorganic adhesive layer and the solar cell is not less than 2.0 mm.
